Emotional intelligence revisited: the questions of level, affective factors and academic performance among generation Z in Malaysia / Kamisah Ariffin ... [et al.] - Ariffin, Kamisah; Abdul Aziz, Roslina; Mohd Mohari, Siti Khadijah; Tahreb, Nurus Syahidah (Universiti Teknologi MARA, 2024)
Research has posited that emotional intelligence (EQ) plays a crucial role in a learner's educational success and is deemed more superior than intelligent Quotient (IQ) in predicting academic achievement. Previous studies indicate an EQ deficiency within the average Generation Z (Gen Z) world view. Within the educational systems, primary focus tends to be directed to the students' cognitive aspects, with less attention on exploring the relationship between emotions and the learning process. This study aimed to address this gap by identifying the EQ levels, factors affecting the EQ levels, and the relationship between EQ and Gen Z academic performance. The study employed a non-experimental quantitative design utilising descriptive and interpretive approach. The participants were 122 Gen Z undergraduates, from a public university in Malaysia. USMEQ-i (Universiti Sains Malaysia EQ inventory) was utilised to obtain the respondents’ EQ levels. The research findings indicate that the participants can be characterised as having a “low high” level of EQ scoring a mean of 2.81, attributed to four affective factors: Emotional Expression, Emotional Conscientiousness, Emotional Maturity, and Emotional Awareness. The findings also reveal no statistically significant correlation between EQ and academic performance. The study concludes the importance of recognising emotional intelligence as a multifaceted construct that influences various aspects of Gen Z students' educational development and maturation. This study holds significant implications for new learning delivery methods, which are further elaborated in the paper.